2016
DOI: 10.3892/ol.2016.4504
|View full text |Cite
|
Sign up to set email alerts
|

Association between FBP1 and hypoxia-related gene expression in clear cell renal cell carcinoma

Abstract: Abstract. Fructose-1,6-bisphosphatase 1 (FBP1) is a rate-limiting enzyme in gluconeogenesis. Recently, the catalytic activity-independent function of FBP1, hypoxia-induced factor (HIF) repression in the nucleus, was identified. The aim of the present study was to investigate the association between FBP1 and hypoxia-related gene expression in clear cell renal cell carcinoma (ccRCC). The protein expression levels of FBP1, HIF-1α, HIF-2α, erythropoietin (EPO) and carbonic anhydrase IX (CA9) were assessed by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
(26 reference statements)
1
18
0
Order By: Relevance
“…They also found that FBP1 antagonizes glycolytic flux to prevent the Warburg effect from occurring [32]. Ning et al observed higher frequencies of low FBP1 expression in tumor tissues in comparison to healthy tissues, as well as an association between low FBP1 expression and high HIF1α and erythropoietin expression in clear cell renal cell carcinoma [34]. This suggests that the effects of FBP1 may be conserved across tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that FBP1 antagonizes glycolytic flux to prevent the Warburg effect from occurring [32]. Ning et al observed higher frequencies of low FBP1 expression in tumor tissues in comparison to healthy tissues, as well as an association between low FBP1 expression and high HIF1α and erythropoietin expression in clear cell renal cell carcinoma [34]. This suggests that the effects of FBP1 may be conserved across tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…In human pancreatic adenocarcinoma, high level PKM2 expression interacts with NF-κB and HIF-1α to induce the activation of HIF target gene VEGF. In contrast to FBP1, PKM2 could function as a coactivator to directly bind with HIF-1α by facilitating the recruitment of p300 [ 16 , 37 , 169 ].
Fig.
…”
Section: Influence Of Intracellular Metabolites On Hif-α Stability Thmentioning
confidence: 99%
“…Particularly, it has become evident that adaptation in metabolite-driven gene regulation may be a potent hallmark to measure tumorigenesis [ 13 15 ]. Hypoxia-inducible factors (HIFs) are heterodimers composed of α subunits and β subunits, where α subunits include HIF-1α, HIF-2α, and the less studied HIF-3α [ 12 , 16 , 17 ]. Under normoxia, two prolines residues of HIF-1α and HIF-2α are hydroxylated by prolyl hydroxylase domain protein 2 (PHD2) and go through ubiquitin-mediated proteolysis via binding to Hippel-Lindau tumor suppressor (VHL) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We noticed a 4‐fold upregulation of FBP1 in group E2 and almost a 3‐fold upregulation in group E1 in the renal cortex. FBP1 is a key gluconeogenesis enzyme and a factor limiting glucose synthesis from non‐sugar compounds (Ning et al, ). Downregulated expression of the LDHB glycolytic enzyme was observed in the renal medulla after administration of fructans in both forms.…”
Section: Discussionmentioning
confidence: 99%
“…We noticed a 4-fold upregulation of FBP1 in group E2 and almost a 3-fold upregulation in group E1 in the renal cortex. FBP1 is a key gluconeogenesis enzyme and a factor limiting glucose synthesis from non-sugar compounds (Ning et al, 2016).…”
Section: Discussionmentioning
confidence: 99%